The Impact of Flow Velocity on Environmental DNA Detectability for the Application in River Systems - Jelle A. Dercksen; Jan Willem Foppen; Astrid Blom; Krijn B. Trimbos; Julia Gebert; Thom A. Bogaard; Laura Maria Stancanelli (Environmental DNA)
ABSTRACT Organisms perpetually release genetic material in their surroundings, referred to as environmental DNA (eDNA), which can be captured and subsequently analyzed to detect biodiversity across the tree of life. In lotic, dynamic environments, little is known about the specific factors that affect the concentration of eDNA between release by the host and its dissemination into the environment. This gap in knowledge introduces significant uncertainty when applying eDNA as a monitoring tool. Our objective is to provide insight on the factors that affect the eDNA concentrations in ecosystems representative of rivers and streams. To this end, we conducted a series of laboratory experiments in a rotating circular (annular) flume, which allows for extended degradation experiments under conditions of flow. Here, we show that flow velocity impacts the observed eDNA concentration over time. Our results suggest that flow‐induced transport keeps eDNA in suspension, reducing eDNA removal from the water column, which increased the observed concentration of eDNA. We observed a temporary increase in eDNA concentration over the early phase of the flume experiment with the highest flow velocity. This increase in eDNA concentration seems to be due to a combination of low eDNA degradation rates and high shear stress, which fragment and subsequently homogenize eDNA particles over the water column. The results of our study show the importance of better understanding and assessing the detection probability of eDNA, both in controlled laboratory and larger‐scale environmental conditions.